SWOT Analysis on New Product Development of PT. XYZ to Enter the International Market - Reva Zahra Aulia (Dinasti Publisher, 2025)
PT XYZ is a fashion company founded in 2022 in South Tangerang, focusing on the production of streetwear, bags, and Muslim clothing. This study aims to develop a new product expansion strategy to the international market through SWOT analysis. Quantitative descriptive methods are used with data collection through literature studies, management interviews, and company document analysis. The analysis was carried out using the IFAS, EFAS, and SPACE matrices. The results show that PT XYZ has the main strengths of unique traditional-modern designs, premium product quality, and strong domestic brand awareness. The main weaknesses include limited production capacity and an immature international distribution system. The biggest opportunities come from global ethnic fashion trends and the growth of international e-commerce, while the main threat is fierce competition from international fashion brands. The IFAS analysis produces a score of 2.86 indicating a fairly strong internal position, EFAS with a score of 3.01 indicating a favorable external environment. The SPACE matrix shows a strategyc position at coordinates (+0.4, +0.6) placing the company in the aggressive quadrant. Strategy recommendations include developing global ethnic collections, expanding international e-commerce, investing in production capacity, and building a global distribution system.